Indications and findings of flexible bronchoscopy in trauma field in Korea: a case series - Dongsub Noh (Journal of Trauma and Injury)
Purpose Since its implementation, flexible fiberoptic bronchoscopy (FBS) has played an important role in the diagnosis and treatment of tracheobronchial tree and pulmonary disease. Although FBS is often performed by endoscopists, it has also been performed by surgeons, albeit rarely. This study investigated FBS from the surgeon’s perspective. Methods This retrospective study included patients who underwent FBS performed by a single thoracic surgeon between March 2017 and December 2021. Accordingly, the epidemiology, purpose, results, and complications of FBS were analyzed. Results A total of 47 patients received FBS, whereas 13 patients underwent repeat FBS. Their mean age was 60.7 years. The main organs injured involved the chest (n=22), brain (n=9), abdominal organ (n=7), cervical spine (n=4), extremities (n=4), and face (n=1). The average Injury Severity Score was 22.5. Indications for FBS included atelectasis or haziness on chest x-ray (n=34), pneumonia (n=17), difficult ventilator management (n=7), percutaneous dilatory tracheostomy (n=3), blood aspiration (n=2), foreign body removal (n=2), and intubation due to a difficult airway (n=1). The findings of FBS were mucous plugs (n=36), blood and blood clots (n=16), percutaneous dilatory tracheostomy (n=3), foreign bodies (n=2), granulation tissue at the tracheostomy site (n=2), tracheostomy tube malposition (n=1), bronchus spasm (n=1), difficult airway intubation (n=1), and negative findings (n=5). None of the patients developed complications. Conclusions FBS is an important modality in the trauma field that allows for the possibility of diagnosis and therapy. With sufficient practice, surgeons may safely perform FBS at the bedside with relative ease.